Superb Lyrebird Menura novaehollandiae mycophagy, truffles and soil disturbance. (21st July 2018) - Elliott, Todd F.; Vernes, Karl
Abstract : We observed foraging behaviour and collected 18 faecal samples of Superb Lyrebirds Menura novaehollandiae at two National Park locations in high‐elevation Nothofagus forests in the New England Tablelands of New South Wales, Australia. Based on microscopic examination of faecal samples, we provide the first report of mycophagy by this bird species. We hypothesize that this association is representative of a much more widespread relation between ground‐foraging birds and fungi. We apply methods not typically used by ornithologists to demonstrate the potential prevalence of mycophagy among ground‐foraging birds and its possible nutritional value. We additionally show the ecological significance that this and associated bird–fungus interactions have in the dispersal of symbiotic fungi.